The Tor Vergata weaning of immunosuppression protocols in stable hepatitis C virus liver transplant patients: the 10‐year follow‐up. (20th December 2012) - Manzia, Tommaso Maria; Angelico, Roberta; Baiocchi, Leonardo; Toti, Luca; Ciano, Paolo; Palmieri, Giampiero; Angelico, Mario; Orlando, Giuseppe; Tisone, Giuseppe
Summary We report herein the 10‐year outcome of the Tor Vergata weaning off immunosuppression protocol in hepatitis C virus (HCV) liver transplant patients. Thirty‐four patients who had received a liver graft for HCV‐related cirrhosis were enrolled in a prospective study in which they were progressively weaned off immunosuppression. The primary endpoints were feasibility and safety of the weaning; the second aim was to assess fibrosis progression. At the 10‐year follow‐up, of the eight original tolerant patients, six remained IS‐free. Of the 26 individuals who could not be weaned, 22 were alive. When the baseline biopsies were compared with the 10‐year biopsies, the tolerant group showed no differences in staging, whereas the nontolerant group showed a significant increase in staging. The fibrosis progression rates calculated for the tolerant and the nontolerant groups were −0.06 ± 0.12 and 0.1 ± 0.2, respectively (P = 0.04). Furthermore, with the last taken biopsies, nine nontolerant patients were showing frank cirrhosis versus no cirrhosis among the tolerant patients. After a 10‐year follow‐up of a Tor Vergata weaning protocol, 6/34 patients completed follow‐up without reinstitution of immunosuppression and this appeared beneficial regarding a reduction in fibrosis progression.